Association of childhood-to-adulthood body size change with cancer risk: UK Biobank prospective cohort - Mandić, Marko; Safizadeh, Fatemeh; Schöttker, Ben; Hoffmeister, Michael; Brenner, Hermann (BMC medicine, 2025)
While excess weight in adulthood and childhood has been associated with increased cancer risk, the link between body size change from childhood to adulthood and cancer risk requires further investigation. We aimed to examine the associations of childhood-to-adulthood body size change with the risk of obesity-related cancers.